Attracting and retaining foreign direct investment: A critical assessment of government policies in Ghana. - Richard Benon-Be-Isan Nyuur (2011)
This thesis explored the critical role of government policies in attracting and retaining Foreign Direct Investment (FDI) in Ghana. The study was motivated by the dearth of research on how government policies influence the attraction and retention of FDI in Sub-Saharan African (SSA) countries. The paucity of studies on this issue is surprising in light of the active role that government policies and agencies have assumed in the last three decades in attracting inward FDI to Africa. This study attempted to fill this gap by using Ghana as a case study to analyse the extent to which government policies have been successful in attracting and retaining FDI in the country. In setting the conceptual and theoretical background of the study, the international business literature on FDI and corporate strategies that guides the activities and decision making of multinational firms in investing abroad was explored and conceptualised, '.;fhe study adopted a mixed method of enquiry. This involvedthe use of questionnaire surveys and semi-structured interviews to collect data from foreign investors in Ghana and government policymakers. Both the quantitative and qualitative data collected was analysed using a variety of methods, including an independent sample t-test, ANOVA, factor analysis, correlations, multiple regression and content analysis. This approach yielded some novel and interesting findings, and provided deeper insights into the role of government in the attraction and retention of FDI. The principal finding of the study was that government policies such as tax, privatization, investment promotion policy, free zone, entry and operations, and the standard of treatment of foreign firms play a critical role in attracting and retaining FDI. In essence, SSA governments have attempted to create an attractive and conducive environment for FDI, but the study revealed that the existence of favourable FDI policies alone is not sufficient in attracting and retaining substantial FDI. It is argued that the policies have to be supported by efficient business facilitation factors, as well as generous incentives. All of these, it is further argued, are necessary for the country to meet the minimum requirement of being competitive enough to attract and retain substantial FDI. The study also revealed that in SSA countries in particular, political and social stability is seen as absolutely crucial to the country's ability to attract and retain FDI. The study also underscored the importance of a marketing strategy, such as the direct targeting of particular investors with specialist expertise to invest in sectors in which Ghana possesses competitive advantage. It is argued that this is the best way for Ghana to attract the right type and amount of FDI into the country. The study thus postulates that such a strategy is more likely to fully reward Ghana with a substantial inflow of FDI that is commensurate with the country's potential. Essentially, a successful inward FDI approach requires the creation of a favourable investment environment that is boosted by direct targeting of investors, and luring them into the important sectors of the SSA nation's economy. The theoretical, methodological and policy contributions and implications of the study are discussed, along with the limitations and areas for future research.